Effect of Temperature on Penetration of Test Liquid into Boiler Pipe - Zaenal Abidin Zaenal Abidin; Setyo Aji Wisnu Wibowo; Tasih Mulyono; Erry Yulian T. Adesta; Agus Geter Edy Sutjipto (International Journal of Engineering Materials and Manufacture, 2023)
Limitations of time in conducting superheater inspections during overhaul, allowing inspectors to conduct liquid penetrant testing activities above pre-determined temperatures. This results in results obtained from the superheater inspection tube boiler indicating a false defect. This study aims to determine the optimal temperature and the impact of testing above the temperature that has been determined in ASME boiler and pressure vessel code using liquid penetrant testing method. This study uses 3 different penetrant brands and test specimens in the form of a superhater tube boiler. Spraying of penetrant fluid is carried out at normal temperature of 30–52oC and above normal temperature is 53–65 oC. The best crack and easy to read image results are tested at 40 °C A, B and C. For testing at temperature 53–65 oC crack thickness level is not clear and hard to read.